Mechatronics with experiments - Cetinkunt, Sabri (West Sussex, United Kingdom : John Wiley & Son, Inc., 2015)
Comprehensively covers the fundamental scientific principles and technologies that are used in the design of modern computer-controlled machines and processes.
EFACE xi ABOUT THE COMPANION WEBSITE xii CHAPTER 1 INTRODUCTION 1 1.1 Case Study: Modeling and Control of Combustion Engines 16 1.2 Example: Electro-hydraulic Flight Control Systems for Commercial Airplanes 31 1.3 Embedded Control Software Development for Mechatronic Systems 38 1.4 Problems 43 CHAPTER 2 CLOSED LOOP CONTROL 45 2.1 Components of a Digital Control System 46 2.2 The Sampling Operation and Signal Reconstruction 48 2.3 Open Loop Control Versus Closed Loop Control 63 2.4 Performance Specifications for Control Systems 67 2.5 Time Domain and S-domain Correlation of Signals 69 2.6 Transient Response Specifications: Selection of Pole Locations 70 2.7 Steady-State Response Specifications 74 2.8 Stability of Dynamic Systems 76 2.9 Experimental Determination of Frequency Response 78 2.10 The Root Locus Method 89 2.11 Correlation Between Time Domain and Frequency Domain Information 93 2.12 Basic Feedback Control Types 97 2.13 Translation of Analog Control to Digital Control 125 2.14 Problems 128 CHAPTER 3 MECHANISMS FOR MOTION TRANSMISSION 133 3.1 Introduction 133 3.2 Rotary to Rotary Motion Transmission Mechanisms 136 3.3 Rotary to Translational Motion Transmission Mechanisms 139 3.4 Cyclic Motion Transmission Mechanisms 143 3.5 Shaft Misalignments and Flexible Couplings 153 3.6 Actuator Sizing 154 3.7 Homogeneous Transformation Matrices 162 3.8 A Case Study: Automotive Transmission as a Gear Reducer 172 3.9 Problems 201 CHAPTER 4 MICROCONTROLLERS 207 4.1 Embedded Computers versus Non-Embedded Computers 207 4.2 Basic Computer Model 214 4.3 Microcontroller Hardware and Software: PIC 18F452 218 4.4 Interrupts 235 4.5 Problems 243 CHAPTER 5 ELECTRONIC COMPONENTS FOR MECHATRONIC SYSTEMS 245 5.1 Introduction 245 5.2 Basics of Linear Circuits 245 5.3 Equivalent Electrical Circuit Methods 249 5.4 Impedance 252 5.5 Semiconductor Electronic Devices 260 5.6 Operational Amplifiers 282 5.7 Digital Electronic Devices 308 5.8 Digital and Analog I/O and Their Computer Interface 314 5.9 D/A and A/D Converters and Their Computer Interface 318 5.10 Problems 324 CHAPTER 6 SENSORS 329 6.1 Introduction to Measurement Devices 329 6.2 Measurement Device Loading Errors 333 6.3 Wheatstone Bridge Circuit 335 6.4 Position Sensors 339 6.5 Velocity Sensors 362 6.6 Acceleration Sensors 365 6.7 Strain, Force, and Torque Sensors 372 6.8 Pressure Sensors 376 6.9 Temperature Sensors 381 6.10 Flow Rate Sensors 385 6.11 Humidity Sensors 393 6.12 Vision Systems 394 6.13 GPS: Global Positioning System 397 6.14 Problems 403 CHAPTER 7 ELECTROHYDRAULIC MOTION CONTROL SYSTEMS 407 7.1 Introduction 407 7.2 Fundamental Physical Principles 425 7.3 Hydraulic Pumps 437 7.4 Hydraulic Actuators: Hydraulic Cylinder and Rotary Motor 457 7.5 Hydraulic Valves 461 7.6 Sizing of Hydraulic Motion System Components 507 7.7 Hydraulic Motion Axis Natural Frequency and Bandwidth Limit 518 7.8 Linear Dynamic Model of a One-Axis Hydraulic Motion System 520 7.9 Nonlinear Dynamic Model of One-Axis Hydraulic Motion System 527 7.10 Example: Open Center Hydraulic System Force and Speed Modulation Curves in Steady State 571 7.11 Example: Hydrostatic Transmissions 576 7.12 Current Trends in Electrohydraulics 586 7.13 Case Studies 589 7.14 Problems 593 CHAPTER 8 ELECTRIC ACTUATORS: MOTOR AND DRIVE TECHNOLOGY 603 8.1 Introduction 603 8.2 Energy Losses in Electric Motors 629 8.3 Solenoids 633 8.4 DC Servo Motors and Drives 640 8.5 AC Induction Motors and Drives 659 8.6 Step Motors 670 8.7 Linear Motors 681 8.8 DC Motor: Electromechanical Dynamic Model 683 8.9 Problems 691 CHAPTER 9 PROGRAMMABLE LOGIC CONTROLLERS 695 9.1 Introduction 695 9.2 Hardware Components of PLCs 697 9.3 Programming of PLCs 705 9.4 PLC Control System Applications 709 9.5 PLC Application Example: Conveyor and Furnace Control 712 9.6 Problems 714 CHAPTER 10 PROGRAMMABLE MOTION CONTROL SYSTEMS 717 10.1 Introduction 717 10.2 Design Methodology for PMC Systems 722 10.3 Motion Controller Hardware and Software 723 10.4 Basic Single-Axis Motions 724 10.5 Coordinated Motion Control Methods 729 10.6 Coordinated Motion Applications 735 10.7 Problems 747 CHAPTER 11 LABORATORY EXPERIMENTS 749 11.1 Experiment 1: Basic Electrical Circuit Components and Kirchoff s Voltage and Current Laws 749 11.2 Experiment 2: Transistor Operation: ON/OFF Mode and Linear Mode of Operation 754 11.3 Experiment 3: Passive First-Order RC Filters: Low Pass Filter and High Pass Filter 758 11.4 Experiment 4: Active First-Order Low Pass Filter with Op-Amps 762 11.5 Experiment 5: Schmitt Trigger With Variable Hysteresis using an Op-Amp Circuit 766 11.6 Experiment 6: Analog PID Control Using Op-Amps 770 11.7 Experiment 7: LED Control Using the PIC Microcontroller 775 11.8 Experiment 8: Force and Strain Measurement Using a Strain Gauge and PIC-ADC Interface 780 11.9 Experiment 9: Solenoid Control Using a Transistor and PIC Microcontroller 787 11.10 Experiment 10: Stepper Motor Motion Control Using a PIC Microcontroller 790 11.11 Experiment 11: DC Motor Speed Control Using PWM 794 11.12 Experiment 12: Closed Loop DC Motor Position Control 799 APPENDIX MATLAB(R), SIMULINK(R), STATEFLOW, AND AUTO-CODE GENERATION 805 A.1 MATLAB(R) Overview 805 A.1.1 Data in MATLAB(R) Environment 808 A.1.2 Program Flow Control Statements in MATLAB(R) 813 A.1.3 Functions in MATLAB(R): M-script files and M-function files 815 A.1.4 Input and Output in MATLAB(R) 822 A.1.5 MATLAB(R) Toolboxes 831 A.1.6 Controller Design Functions: Transform Domain and State-Space Methods 832 A.2 Simulink(R) 836 A.2.1 Simulink(R) Block Examples 843 A.2.2 Simulink(R)S-Functions in C Language 852 A.3 Stateflow 856 A.3.1 Accessing Data and Functions from a Stateflow Chart 865 A.4 Auto Code Generation 876 REFERENCES 879 INDEX 883
Includes bibliographical references.
Keywords: MECHATRONICS